Treatment of W. bancrofti (Wb) in HIV/Wb coinfections in South India. - Kawsar R Talaat; Subash Babu; Pradeep Menon; N Kumarasamy; Jabin Sharma; Jeeva Arumugam; Kalaivani Dhakshinamurthy; Ramalingam Srinivasan; S Poongulali; Wenjuan Gu; Michael P Fay; Soumya Swaminathan; et al. (PLoS Neglected Tropical Diseases, 2015)
BACKGROUND:The disease course of human immunodeficiency virus (HIV) is often altered by existing or newly acquired coincident infections. METHODOLOGY/PRINCIPAL FINDINGS:To assess the influence of pre-existing Wuchereria bancrofti infection on HIV progression, we performed a case-controlled treatment study of HIV positive individuals with (FIL+) or without (FIL-) W. bancrofti infection. Twenty-eight HIV+/FIL+ and 51 matched HIV+/FIL- subjects were treated with a single dose of diethylcarbamazine and albendazole (DEC/Alb) and followed for a year at regular intervals. Sixteen of the HIV+/FIL+ subjects (54%) and 28 of the HIV+/FIL- controls (57%) were on antiretroviral therapy (ART) during the study. Following treatment, no differences were noted in clinical outcomes between the 2 groups. There also was no significant difference between the groups in the HIV viral load at 12 months as a percentage of baseline viral load (HIV+/FIL+ group had on average 0.97 times the response of the HIV+/FIL- group, 95% CI 0.88, 1.07) between the groups. Furthermore, there were no significant differences found in either the change in viral load at 1, 3, or 6 months or in the change in CD4 count at 3, 6, or 12 months between the 2 groups. CONCLUSIONS/SIGNIFICANCE:We were unable to find a significant effect of W. bancrofti infection or its treatment on HIV clinical course or surrogate markers of HIV disease progression though we recognized that our study was limited by the smaller than predicted sample size and by the use of ART in half of the patients. Treatment of W. bancrofti coinfection in HIV positive subjects (as is usual in mass drug administration campaigns) did not represent an increased risk to the subjects, and should therefore be considered for PLWHA living in W. bancrofti endemic areas. TRIAL REGISTRATION:ClinicalTrials.gov NCT00344279.